Effect Of Heat Welding GTAW (Gas Tungsten Arc Welding) In Grade 316L Stainless Steelmaterial Properties Of Violence (Hardness) And Composition Material - Surya I (Bandar Lampung University (UBL), 2017)
Welding on the type of welding (welding) using the GTAW (Gas Tungsten Arc Welding). It is one of the most widely used method for connecting a material, especially on the pipe. Splicing by welding is one way to provide heat to the material so that the material melted and fused. In stainless steel material will be very easily distracted from the heat during the welding.So it can affect the properties of the stainless steel material especially for the nature of the corrosion resistance. This study aims to understand and minimize the effect of heat from the weld on the composition of the metal alloy stainless steel (SS),especially for atomic Chromium (Cr) and violence (Hardness). Experiments were carried out by testing the hardness(Hardness test) and PMI Test on area base material, HAZ (Heat Affected Zone) and the weld metal. The results obtained in the form of data in tabular form to inform a large percentage of the value of the level of violence and in this case the percentage composition of the chromium material to the readings of test points that have been determined from the test material